Categorical and concept apparatus for the transformation of catering enterprises’ marketing strategies - V. M. Sedelnikov (Вестник университета)
The article presents the results of a study of the transformation processes of catering enterprises’ marketing strategies. In particular, the study considers the views of domestic and foreign scholars concerning the definitions of the concepts of “loyalty”, “satisfaction” and “engagement”. It has been argued that they are complementary and mutually reinforcing. The main approaches to the marketing strategies transformation (product-oriented, customer-oriented and value-oriented) have been identified, the change of targets in the formation and implementation process of the marketing strategies (from focusing on the company’s product to focusing on interaction with consumers) has been reflected, and that constitutes in whole the scientific novelty of the study. From the standpoint of a value-oriented approach, the marketing strategy concept has been clarified as a system of strategic actions for the development of a company, which aims to form long-term relationships with consumers and increase their level of involvement, satisfaction and loyalty throughout the entire period of interaction with the consumer (customer life-time cycle). As a direction for further research, is indicated an assessment of the satisfaction, involvement and loyalty influence level on the implementation effectiveness of catering enterprises’ marketing strategies.